WP4 Towards a multi stakeholder to approach breeding : priorities for landrace-derived elite Barley in Ethiopia - Najjar, Dina; Tsige Abebe, Meseret; Oueslati, Dorsaf; M. Oumer, Ali (2024)
The overall aim is to deliver high-yielding barley genotypes with tolerance to biotic and abiotic stresses and adapted to Ethiopian environments and their constraints. This will ensure stable access to food/malt and feed for smallholder farmers, well-being outcomes (such as better nutrition and drudgery and poverty reduction) and at the same time increasing resilience to new climate-related constraints. To ensure adaptation to local practices and facilitate the adoption of elite genotypes tested, farmer preferences, both men and women, will be integrated together with field trial and genomic data into the final selections.